A theoretical study of the fundamental torsional wave in buried pipes for pipeline condition assessment and monitoring. (21st July 2016) - Muggleton, J.M.; Kalkowski, M.; Gao, Y.; Rustighi, E.
Abstract: Waves that propagate at low frequencies in buried pipes are of considerable interest in a variety of practical scenarios, for example leak detection, remote pipe detection, and pipeline condition assessment and monitoring. Whilst there has been considerable research and commercial attention on the accurate location of pipe leakage for many years, the various causes of pipe failures and their identification, have not been well documented; moreover, there are still a number of gaps in the existing knowledge. Previous work has focused on two of the three axisymmetric wavetypes that can propagate: the s =1, fluid-dominated wave; and the s =2, shell-dominated wave. In this paper, the third axisymmetric wavetype, the s =0 torsional wave, is investigated. The effects of the surrounding soil on the characteristics of wave propagation and attenuation are analysed for a compact pipe/soil interface for which there is no relative motion between the pipe wall and the surrounding soil. An analytical dispersion relationship is derived for the torsional wavenumber from which both the wavespeed and wave attenuation can be obtained. How torsional waves can subsequently radiate to the ground surface is then investigated. Analytical expressions are derived for the ground surface displacement above the pipe resulting from torsional wave motion within the pipe wall. A numerical model is also included, primarily in order to validate some of the assumptions made whilst developing the analytical solutions, but also so that some comparison in the results may be made. Example results are presented for both a cast iron pipe and an MDPE pipe buried in two typical soil types.